REKONSTRUKSI KONSEP KEBEBASAN HAK BERSERIKAT BAGI SERIKAT PEKERJA PADA HUBUNGAN INDUSTRIAL BERBASIS NILAI KEADILAN - Gunarto Gunarto (Faculty of Law, Universitas Jenderal Soedirman, 2010)
The concept of freedom of association for trade union rights provided for in Law No. 21 of 2000 on Trade Unions, aimed at providing protection of workers, and improve the welfare of workers. But social facts to still many industrial dispute, and there were so many layoffs. Legal research methods to use social research. So in this perspective, freedom of association for trade union rights are not viewed from the norms of the country, but seen from the values of living in society, although freedom of association rights are influenced by state regulations. Construction of freedom of association for trade union rights as set out in Law No. 21 of 2000 on Trade Unions, still reflects the capitalistic character. The impact caused the number of industrial disputes and layoffs for workers, because employers view workers as a factor of production rather than as business partners. So the necessary reconstruction of freedom of association rights for workers with social justice based values to create a harmonious industrial relations. A reconstruction model using prismatic law, which took a good system of capitalistic model and the socialist model and the model adapted Pancasila industrial relations with the values of Indonesian.Keywords : Reconstruction, Freedom Right of Association, trade unions, justice